New power factor correction technique in switched reluctance motor drive using PWM converter. (2015) - Naruka, Mahavir Singh; Singh, S.N.
This paper present the power factor improvement technique in the midpoint converter-based switched reluctance motor (SRM) drive using an AC-DC three level pulse width modulation (PWM) converter. A conventional SRM drive produces very high level of harmonics content and poor power factor at AC mains. The proposed converter with midpoint converter fed SRM drive improves the power factor at AC mains with low current harmonics. The SRM drive with converter is modelled and its performance is simulated in MATLAB/Simulink environment.